Carrot slice test: A reliable method for evaluating the tumorigenicity of Pseudomonas savastanoi pv. nerii - Attila Fodor; Áron Juhasz; Viktória Vitári; Karacs-Végh Anita (Open Journal of Bacteriology - Peertechz Publications, 2024)
Pathogenicity studies on oleander plants take a long time and require significant costs to confirm the identification of isolates and to verify their pathogenicity. In this study, the carrot slice test was used as a rapid method for Pseudomonas savastanoi pv. nerii. The test is suitable for the investigation of tumorigenicity of 25 Pseudomonas savastanoi pv. nerii isolates from different parts of Hungary. On carrot slices, the first characteristic knots were observed 7 days after inoculation and were fully developed 16 days after inoculation. The one-year oleander plants used to confirm the pathogenicity of the bacteria were inoculated with a bacterial suspension to confirm the reliability of the carrot slice test. Characteristic symptoms of knots were observed on all oleander plants 46 days after inoculation. The results showed that the carrot slice method is a straightforward, rapid, and reliable method for testing and confirming tumor formation of Pseudomonas savastanoi pv. nerii without plants.